MODERN PERSONNEL MANAGEMENT TECHNOLOGIES - RUDNICHENKO, Yevhenii; HAVLOVSKA, Nataliia; LUTIUK, Vasyl; CHAINSKA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the theoretical provisions of personnel management and the main types of personnel management technologies. Author’s definition of "personnel", "personnel management", "technology" and "personnel management technologies" is given. In particular, personnel should be understood as a set of employees, employees of the organization, who hold certain positions and possess the necessary qualifications, knowledge or have practical experience, etc.; the concept of personnel management should be understood as a specific field of managerial activity, a process, a purposeful activity, a systemic, systematically organized influence, a part of the functional area where the main object is people, and all activities are directed to the object (people) in order to increase the efficiency of the use of potential workforce and achieving the set goal; technologies should be understood as different means (methods, processes, etc.) that ensure a change in state, properties, etc. in the course of activity; personnel management technologies should be understood as the process of selection, motivation, training, development and evaluation of personnel using various methods in order to achieve the goals set for the organization by ensuring the best results of labor activity. The main elements characterizing the concept of "personnel" are singled out, they include the existence of labor relations based on legal norms provided for by state legislation and providing for labor remuneration; possession of certain characteristics - education, seniority, qualification, professional qualities, experience, etc.; targeted orientation of personnel to achieve a certain strategic goal of the organization’s functioning within the scope of their job duties. Personnel management technologies should be divided into personnel selection technologies; personnel motivation technologies; training and personnel development technologies; personnel evaluation technologies, which are described in the article. Recruitment technologies include: outplacement, video interview, gamification in recruiting, internet sourcing, talent search, preliminary screening, recruiting, candidate tracking systems (ATS), screening, headhunting. Personnel motivation technologies include: grading (grade - degree, class, rank), golden parachute, career chart, MVO (management by objectives) method, Comp&ben (Compensation & Benefits), KPI (Key Performance Indicators), Pay for Performance. Training and personnel development technologies include: case study, coaching, ISA training model (income share agreement), training, self-study, E-learning. Personnel evaluation technologies include: 360 degrees, RACI matrix, SHLTOOLS online system, mystery shopper, checklist, performance review.